Gut Microbiota as a Critical Modulator of Host Immune Responses in Severe Infections: Mechanistic Insights and Therapeutic Implications - Chaiyasit, Anan; Wattanakul , Siriporn; Rattanapong , Kittisak (Journal of Society Medicine, 2026)
Introduction: Severe infections, including sepsis and acute respiratory distress syndrome (ARDS), are the leading causes of morbidity and mortality worldwide, driven by dysregulated host immune responses. Emerging evidence has identified the gut microbiota as a critical regulator of systemic immunity; however, its mechanistic role in severe infection remains unclear. Methods: This narrative review synthesizes evidence from PubMed, Scopus, and Web of Science, focusing on mechanistic, translational, and clinical studies that evaluated microbiota–immune interactions in severe infections. Relevant studies were critically appraised and integrated to generate a mechanistic and clinically meaningful synthesis. Results: The gut microbiota maintains immune homeostasis through metabolites, such as short-chain fatty acids, bile acids, and tryptophan derivatives, which regulate epithelial integrity and T cell differentiation. In critical illness, dysbiosis, characterized by reduced diversity, loss of commensals, and pathogen overgrowth, disrupts these processes, leading to increased intestinal permeability, systemic inflammation, and organ dysfunction. Gut–organ axes, including gut–lung, gut–brain, and gut–kidney pathways, further amplify disease severity. Clinical evidence links dysbiosis to higher mortality and prolonged intensive care unit stays. Microbiota-targeted therapies, including probiotics, fecal microbiota transplantation, and precision interventions, show promise but remain limited by heterogeneity and insufficient high-quality evidence. Conclusion: Gut microbiota is a central modulator of host responses in severe infections, linking intestinal dysregulation and systemic immune dysfunction. Targeting microbiome-related pathways represents a promising strategy for precision critical care, although further mechanistic and clinical studies are required to establish effective therapies, improve patient outcomes in critical illness settings, and advance microbiome-based precision medicine.